Dampak Pemasaran Aplikasi Seluler Augmented Reality: Memanfaatkan Pengalaman Sosial Bersama untuk Pemasaran Viral - Anggraeni Woro Hapsari (Jurnal Syntax Admiration, 2024)
In today's business landscape, technology plays a pivotal role, enabling a shift from traditional to digital marketing practices. Augmented reality (AR) technology has emerged as a promising tool to enhance consumer experiences and influence purchase decisions. This study examines the impact of aesthetics, entertainment, education, escapism, AR marketing satisfaction, shared social experiences, and purchase intention on AR mobile applications in Indonesia. Data collected through online questionnaires were analyzed using SEM-PLS, revealing significant effects across all variables. Aesthetic elements positively influenced entertainment, education, and escapism, subsequently enhancing AR marketing satisfaction. Furthermore, AR marketing satisfaction positively affected shared social experiences and purchase intention.